Cover design and its impact on consumer purchasing decision-making: an analytical study of the opinions of a sample of employees at Nour Al-Kafeel General Trade and Animal Products Company in the Holy Governorate of Karbala - نغم دايخ عبد علي; عبير محمد مهدي (Iraqi Journal for Administrative Sciences, 2024)
this research addressed the role which play packaging design in consumer’s buying decision making , the higher dynamic in market condition and level of consumer’s taste push the business organizations to importance in achieve the differences in it’s products design as compared with rival’s product .the problem’s research expressed in questions about range of effect packaging design and it’s dimensions in consumer’s buying decision makingin simple from workers in noor alkafeel company for general trading and animals product , the research aims to achieve some of goals according to the main and sub hypothesis , and used questionnaire to collect data and information about this simple, which distributed on simple formulate in )30( persons included staff )employee, division manager and department manager who works in this company, and for process this data used several statistical methods and represented by a factor of linear correlation of pearson)pearson correlation( as well as linear regression . the statistical methods shown a number of results from the most prominent is having a significant effect between packaging design and consumer’s buying decision makingin . in the light of discussion the results showed the big importance to packaging design and consumer’s buying decision makingin concept , this will need more care from the company in packaging design because it’s role in consumer’s buying decision makingin .